(untitled) (Indian Journal of Experimental Biology (IJEB), 2021)
In ornamental fishery, for commercialization and efficient propagation of fish species in demand, controlling their sex, male or female, plays an important role as it influences reproduction, growth and product quality. In one such common aquarium fish, dwarf gourami, Trichogaster lalius (Hamilton, 1822), males look more attractive and fetch better market price encouraging masculinization of this species. In the present study, we evaluated the effect of anastrozole on masculinization potential in T. lalius. The experiment consisted of two trials, in trial 1; anastrozole was incorporated into feed at 50, 100, 150 and 200 mg/kg and fed to first feeding fry for 50 days. In trial 2, immersion treatment of anastrozole was carried out at different doses of 250, 500, 750 and 1,000 μg/L for 3 h each on 3rd, 5th and 8th day of post-hatching. Oral administration of anastrozole resulted in 90.32% masculinization at 200 ppm and the immersion treatment of anastrozole produced 100% masculinization at 1000 μg/L. Histological sections indicated that the anastrozole treatments suppressed ovarian development, leading to the atretic oocytes. However, the testicular development was unaffected. Testosterone level increased whereas estradiol level decreased with increased dose of the chemical. Cortisol level also showed a significant increase in male with increased doses of anastrozole, indicating stress which in turn helped to synthesize the testosterone. The results show that the immersion treatment of anastrozole is more effective than oral administration in inducing masculinization in T. lalius.